Association of -24CT, 1249GA, and 3972CT ABCC2 Gene Polymorphisms with Methotrexate Serum Levels and Toxic Side Effects in Children with Acute Lymphoblastic Leukemia. (1st March 2014) - Sharifi, Mohamad Jafar; Bahoush, Gholamreza; Zaker, Farhad; Ansari, Shahla; Rafsanjani, Khadijeh Arjmandi; Sharafi, Heidar
<x xml:space="preserve">Abstract</x> Acute lymphoblastic leukemia patients after being treated with methotrexate, have differences in methotrexate serum levels and toxic side effects. One of the main determinants of these toxic side effects is the host pharmacogenetics. The aim of this study was to evaluate the association of -24CT, 1249GA, and 3972CT ABCC2 gene polymorphisms with serum levels, and toxic side effects of methotrexate in childhood acute lymphoblastic leukemia. Applying polymerase chain reaction and restriction fragment length polymorphism techniques, the prevalence of -24CT, 1249GA, and 3972CT ABCC2 gene polymorphisms was evaluated in 65 acute lymphoblastic leukemia patients. The relationship between polymorphisms and methotrexate serum levels and toxicities was studied. A reverse significant relationship was detected between 3972T allele carriers and hepatotoxicity (P = 0.01, OR = 0.25, 95% CI = 0.09–0.72). Also, 1249A allele carriers had increased rate of gastrointestinal toxicity (P = 0.05, OR = 3.47, 95% CI = 1.04–11.57). No significant relationship was detected between -24CT polymorphism and methotrexate toxic side effects. There was no significant relationship between these three polymorphisms and methotrexate serum levels. Genotyping for 3972CT and 1249GA ABCC2 gene variants maybe useful in acute lymphoblastic leukemia to optimize methotrexate therapy and reducing the associated toxicity.